2015
DOI: 10.1093/carcin/bgv146
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation in non-small cell lung cancer-associated fibroblasts

Abstract: SummaryDNA methylation profiling of TAFs reveals global demethylation and a selective impact on the TGF-β pathway. Moreover, it suggests the fibrocyte origin of a fraction of TAFs, and identifies a novel prognostic biomarker in non-small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
99
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(120 citation statements)
references
References 52 publications
14
99
1
Order By: Relevance
“…Notably, we found no evidence of the global hypomethylation that typically occurs in tumor epithelial cells (Supplemental Fig. S1E,F) and as previously reported for CAFs from gastric and non-small cell lung cancers (Jiang et al 2008;Vizoso et al 2015).…”
Section: Bph-1+npfsupporting
confidence: 82%
See 1 more Smart Citation
“…Notably, we found no evidence of the global hypomethylation that typically occurs in tumor epithelial cells (Supplemental Fig. S1E,F) and as previously reported for CAFs from gastric and non-small cell lung cancers (Jiang et al 2008;Vizoso et al 2015).…”
Section: Bph-1+npfsupporting
confidence: 82%
“…Here we ask if genome-wide differences in the epigenome underpin the persistent phenotypic differences between CAFs and NPFs. Earlier studies using low-resolution techniques found examples of DNA methylation changes in CAFs or tumor stroma from various cancer types (Hu et al 2005;Fiegl et al 2006;Hanson et al 2006;Rodriguez-Canales et al 2007;Dawsey et al 2008;Jiang et al 2008;Banerjee et al 2014;Vizoso et al 2015). However, the full epigenome landscape of CAFs remains uncharted, so the precise epigenetic changes and their contribution to altered transcriptional patterns is unknown.…”
Section: Australiamentioning
confidence: 99%
“…These hypermethylated genes (homeobox A9 (HOXA9) and HOXB6) were independently validated by bisulfite sequencing. Genome-wide human methylation microarray analysis was conducted on CAFs and paired control fibroblasts from non-small cell lung cancer patients by Vizoso et al (2015). Compared with normal fibroblasts, they found global DNA hypomethylation in CAFs accompanied by some hypermethylated genes.…”
Section: Dna Methylation In Cancer-associated Fibroblastsmentioning
confidence: 99%
“…CAFs were shown to promote tumor progression and invasion through secreting the protumoral growth factor IGF-1 (Mueller and Fusenig, 2004;Ahmed and Farquharson, 2010). Vizoso et al (2015) identified hypermethylationassociated SMAD family member 3 (SMAD3) silencing in CAFs, which was associated with aberrant response to exogenous TGF-β1. Exogenous TGF-β1 can induce contractility and ECM expression in CAFs, but not in normal fibroblasts, suggesting that SMAD3 silencing promotes hyperresponsiveness to TGF-β in CAFs.…”
Section: Dna Methylation In Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Thus, regardless of the initiating insult, myofibroblasts share common markers like the fibroblast-activation protein and α-smooth muscle protein and, importantly, maintain a stable phenotype when severed from the cellular source of their generation (12,13). This phenotypic durability relies on the reprogramming of their epigenetic landscape (11,(14)(15)(16)(17), a well attested genomic signature in CAFs (18)(19)(20)(21).…”
Section: The Myofibroblast In Cancer Stroma and In Non-neoplastic Chrmentioning
confidence: 99%